"Mystical Theology" in Aquinas - Dvořák, Petr (European journal for philosophy of religion, 2022)
The paper explores two avenues to the union of the believer with God in Thomas Aquinas inspired by Pseudo-Dionysius the Areopagite; namely, the intellectual union in faith through the gift of understanding and the union in charity as the basis for the knowledge associated with the gift of wisdom. The former amounts to an intellectual grasp of revealed truths without full understanding of the terms used (without the apprehension of the essences), yet with a clear understanding of what would be erroneous interpretations and meanings. The latter is an (quasi-)experimental knowledge of God based on connaturality with him due to the infused virtue of charity. Both kinds of knowledge or "mystical theology" are open to any believer in the state of sanctifying grace and are its effects.